Circulating extracellular vesicles: Their role in tissue repair and regeneration. Issue 1 (August 2016) - Teixeira, José H.; Silva, Andreia M.; Almeida, Maria Ines; Barbosa, Mário A.; Santos, Susana G.
Abstract: Extracellular vesicles (EVs) have been a growing interest of the scientific community in recent years due to the wide possibilities of their evaluation as biomarkers of disease, and their potential to be used as therapeutic agents or vehicles. EVs that circulate in plasma carry proteins and nucleic acids, potentially to distant locations in the body where they can interfere with several cellular processes. To aid understanding of this rapidly evolving field, circulating EVs, including immune cell-derived ones, are reviewed here. Their cellular origins and described functions are discussed in a perspective of their contribution to regenerative processes. Different techniques for EV engineering and examples of their application are reviewed as a strong future direction of EV research. A summary of important aspects yet to be addressed ties up this review.